Measuring Social Studies Critical Roles of Empowering Student’s Civic Competence in Overcoming Gender Issues to Enhance Sustainable New World - Adeduntan, Ronke Iyabo; Adetayo, Janet Oyebola (Interdisciplinary Journal of Education, 2022)
The escalating reports of gender issues, particularly violence against women and girls across Nigeria, through the media are worrisome. This raises further questions on the roles of Social Studies in overcoming these concerns hindering societal peace for sustainable development. The researchers adopted a descriptive design to examine the knowledge and attitudes including social skills standards gained from Social Studies to help realize a new world order on gender issues in the society. A sample size of 200 respondents was chosen through a non-probability sampling method using a purposive sampling technique. The study adopted a quantitative method approach for data collection. The findings revealed high knowledge awareness of gender issues among respondents while attitudes and social skills gained recorded only moderate level of knowledge awareness. Also, findings showed a statistically significant difference between students’ knowledge of gender issues and their social skills for emotional intelligence to deal with gender issues around them. Recommendations were made for teachers to scale up lesson emphasis towards helping students to develop required soft skills as solutions in responding to gender issues around them.